LearnVis: Analyzing Higher Education Student Performance through Information Visualization Techniques - Oliveira, Angélica Gomes; Gabriel, Paulo Henrique Ribeiro; Paiva, José Gustavo de Souza (Journal of the Brazilian Computer Society, 2026)
Understanding educational challenges in higher education requires a detailed analysis of the variables related to academic performance, such as grades, attendance, and student engagement. This analysis is crucial for identifying critical factors that affect learning and student retention. In this context, this study introduces LearnVis, a visual analytics system developed to analyze student performance in higher education. The system was designed to utilize data from university academic records, including grades, attendance, and engagement with specific topics. It offers a set of coordinated layouts that enable the analysis of both student groups and individuals. These layouts allow users to explore the structure of course modules, considering the topics they comprise and their sequence throughout the course. Additionally, the system facilitates the analysis of student behavior in each module, including their attendance in the topics covered, their respective grades, and the tracking of multiple attempts in specific modules, as well as their completion sequences. To evaluate its effectiveness, the LearnVis system was applied to a dataset of 1,490 students from the Computer Information Systems program at the Federal University of Uberlândia, covering the period from 2009 to 2019. The results demonstrate that the system provides valuable insights that contributes to improve academic performance and decrease student retention.